1992
DOI: 10.1088/0029-5515/32/1/i04
|View full text |Cite
|
Sign up to set email alerts
|

Shear reversal and MHD activity during pellet enhanced performance pulses in JET

Abstract: Analysis of MHD activity in pellet enhanced performance (PEP) pulses is used to determine the position of rational surfaces associated with the safety factor q. This gives evidence for negative shear in the central region of the plasma. The plasma equilibrium calculated from the measured q values yields a Shafranov shift in reasonable agreement with the experimental value of about 0.2 m. The corresponding current profile has two large off-axis maxima in agreement with the bootstrap current calculated from the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
113
0

Year Published

1996
1996
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 199 publications
(116 citation statements)
references
References 14 publications
3
113
0
Order By: Relevance
“…4 for q = 3, s^ = -0. 5 Similar to what was found in the fluid theory for the PVS mode in cold plasmas, the stabilizing effects of the negative magnetic shear are strongest for lower q plasmas. For example, for q = 1.5, 7/w+, -0.4, at s^ = 0.5 while -0.2 for s^ = -0.5.…”
Section: A Magnetic Shear Variationsupporting
confidence: 68%
“…4 for q = 3, s^ = -0. 5 Similar to what was found in the fluid theory for the PVS mode in cold plasmas, the stabilizing effects of the negative magnetic shear are strongest for lower q plasmas. For example, for q = 1.5, 7/w+, -0.4, at s^ = 0.5 while -0.2 for s^ = -0.5.…”
Section: A Magnetic Shear Variationsupporting
confidence: 68%
“…A carefully MHD analysis of the JET PEP mode [124] -a representative of the peaked density profile confinement category -showed that also in this case the q-profile seems to be reversed. Specifically, the density gradient is very effective in flattening the qprofile.…”
Section: The Universal Role Of Shear Flow Decorrelation [47]mentioning
confidence: 89%
“…The pellet enhanced performance ͑PEP͒ mode 16 was achieved in the Joint European Torus. 17 In the PEP mode, central deposition from pellet fueling and central heating in the ion cyclotron range of frequencies can lead to strongly peaked density profiles that produce the ITBs with the negative shear region in the plasma core.…”
Section: Introductionmentioning
confidence: 99%